(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The purpose of the current research is to identify the role of maturity in knowledge management represented by (individuals, processes, and technological skills) in the institutional performance of (employee satisfaction, productivity improvement, and growth), and accordingly a sample of the (58) senior leaderships of the University of Babylon were selected. A leader in order to identify the level of availability of knowledge management maturity, and attention to institutional performance, which means the necessity of demonstrating the tools that are used in order to demonstrate the results of the study, and accordingly, the most famous statistical tools that were used for this purpose were (the structural modeling equation, The Cronbach alpha coefficient, the normal distribution represented by the tests "Kolmogorov-Smirnov, Shapiro-Wilk", the arithmetic mean, the standard deviation, the Pearson correlation coefficient, and the regression coefficients that were extracted by means of the program "AMOS.V.24". Based on the results of the study, the study has concluded It was found that there is a correlation and moral influence between the maturity of knowledge management and the institutional performance of the university, which requires the research sample to work on investing its knowledge potentials in order to develop and improve its institutional performance.